Thyroid Mutations and Implications for Clinical Treatment - Emily S. Zhang; Joseph Scharpf (Journal of Head & Neck Physicians and Surgeons)
This article provides an overview of the evolving paradigm in the management of aggressive thyroid cancer. While differentiated thyroid cancer (DTC) generally has a favorable prognosis, subsets such as radioactive iodine-refractory DTC, medullary thyroid cancer, and anaplastic thyroid cancer present significant challenges with high mortality rates. The identification of aggressive diseases through molecular testing has revolutionized risk stratification and treatment options, allowing for targeted therapies that match-specific genetic alterations. DTCs can have BRAF-like or RAS-like pathways of driver mutations with strong genotype–phenotype correlations, which are targetable through multikinase and tyrosine kinase inhibitors. Case studies illustrate how molecular profiling can guide clinical decisions and enhance treatment outcomes. Ultimately, the incorporation of genetic insights into clinical practice is essential for improving management strategies, minimizing overtreatment, and optimizing patient care in advanced thyroid cancer.